Protein kinase D at the Golgi controls NLRP3 inflammasome activation - Zhang, Zhirong; Meszaros, Gergö; He, Wan-ting; Xu, Yanfang; de Fatima Magliarelli, Helena; Mailly, Laurent; Mihlan, Michael; Liu, Yansheng; Puig Gámez, Marta; Goginashvili, Alexander; Pasquier, Adrien; Bielska, Olga; et al. (The Journal of experimental medicine, 2017)
The inflammasomes are multiprotein complexes sensing tissue damage and infectious agents to initiate innate immune responses. Different inflammasomes containing distinct sensor molecules exist. The NLRP3 inflammasome is unique as it detects a variety of danger signals. It has been reported that NLRP3 is recruited to mitochondria-associated endoplasmic reticulum membranes (MAMs) and is activated by MAM-derived effectors. Here, we show that in response to inflammasome activators, MAMs localize adjacent to Golgi membranes. Diacylglycerol (DAG) at the Golgi rapidly increases, recruiting protein kinase D (PKD), a key effector of DAG. Upon PKD inactivation, self-oligomerized NLRP3 is retained at MAMs adjacent to Golgi, blocking assembly of the active inflammasome. Importantly, phosphorylation of NLRP3 by PKD at the Golgi is sufficient to release NLRP3 from MAMs, resulting in assembly of the active inflammasome. Moreover, PKD inhibition prevents inflammasome autoactivation in peripheral blood mononuclear cells from patients carrying NLRP3 mutations. Hence, Golgi-mediated PKD signaling is required and sufficient for NLRP3 inflammasome activation.